A prospective study on the use of anesthetic agents in modern surgical practice at a tertiary care hospital, Karnataka, India - Ganguly, Deeptangshu; Ranganath, Dharani D.; Herle, Manohar; C. H., Rajasekhar; Nagaraj, Kokila B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The choice of local anesthetic is based on potency of the agent, onset and duration of anesthesia, and side effects of the drug Objectives of the study were, the study proposes to analysis the pattern, trend, rationality and frequency of use of anesthetic agents in modern surgical procedures. Methods: The study records relevant data obtained from surgical case records of patients from department of General surgery, Obstetrics and Gynecology and Orthopedics during the period December 2014 to May 2015 including first one month of pilot study, at KVGMC, Sullia (D.K), Karnataka. Results: A total of 744 cases were collected and screened according to inclusion and exclusion criteria and finally 348 cases were recorded and critically analysed. Sub-arachnoid block is the most common type of anesthetic procedure (75.28%) performed by the anesthetists. Of 348 cases undergoing anesthesia using local anesthetic agents, 228 cases required only a single agent and 120 cases required a combination anesthetic agents. 206 underwent sub-arachnoid block, 16 epidural block (EPID) and only 2 brachial block. The most commonly used agent for maintainence of general anesthesia is Isoflurane (68%) followed by Halothane (32%) and the combination of skeletal muscle relaxants were Succinylcholine with either Atracurium (39.8%) or Vecuronium (37.16%). Analgesics were the most commonly used adjuvants followed by ondansetron. Conclusions: The study showed that the most common anesthetic procedure performed using local anesthetic agents is SA/SAB block and the most common agent used is bupivacaine which was frequently employed at the dose range of 3-4 ml. There was significant association found between the no. of anesthetic agents used and the type of anesthetic procedure performed and also between the concerned department and the type of anesthetic procedure performed. Thus, the rationality in the usage of relevant anesthetic agents with appropriate adjuvants is evident.